A Review of groundwater arsenic contamination in Bangladesh: the millennium development goal era and beyond - Md. Yunus, Fakir; Khan, Safayet; Chowdhury, Priyanka; Hasnat Milton, Abul; Hussain, Sumaira; Rahman, Mahfuzar (© 2016 MDPI AG, 2016)
This article was published in International Journal of Environmental Research and Public Health [© 2016 MDPI AG] and the definite version is available at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC4772235/